Vajirayana Tale: Role to Society Kreekamon Nookur Nition Pornumpaisakul - หนูเกื้อ กรีกมล; พรอำไพสกุล นิธิอร (Academic and Research Journal of Liberal Arts (Online), 2018)
A study of Vajirayana Tale roles in Thai society was the objective of this research. The results indicated that Vajirayana Tale played three roles in Thai society—creating enjoyment, providing knowledge and comment, and as media to critique and persuade society. The first role to create enjoyment was generated from characters, stories, and scenes. The second role was to provide knowledge and comment any such as providing knowledge in Thai idioms, providing comment any on the prudence, providing advice to government officials, and providing comment any on the harmony. In the third role it was found that media had roles to critique and persuade society namely, not to believe in the supernatural (i.e. not believe in ghosts) which was derived from criticism and persuasion. In addition, public relation and dissemination of new things in society (i.e. railroad, car, and banknote) also resulted from their role as media to critique and persuade society. Therefore, Vajirayana Tale was the valuable literature for both Thai society and readers. Readers not only got enjoyment from reading them, but also knowledge. Moreover, realizing the new things that occur in society was also achieved.